2019
DOI: 10.18553/jmcp.2019.25.8.927
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacist-Managed Antidiabetic Deprescribing Program in an Integrated Health Care System

Abstract: BACKGROUND: In the elderly, use of medications may increase the propensity for adverse drug events due to alterations in pharmacokinetic and pharmacodynamic profiles from normal aging processes. Deprescribing is the planned and supervised process of dose reduction or discontinuation of medications that may lead to harm or are no longer beneficial. While there are studies detailing strategies to deprescribe medications such as benzodiazepines and antipsychotics in nursing homes or for patients with dementia, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 24 publications
0
35
0
2
Order By: Relevance
“…[163][164][165][166][167][168][169] Different projects have been working towards improving the health system, at all levels (primary care, hospitals or specialized institutes) and working with all stakeholders (health workers, managers, regional health directors) to improve access to care, increase availability and affordability of medicines, improve coordination of care or improve patient satisfaction. [170][171][172][173] Given the comorbidity between mental health and cardiometabolic conditions, some projects have promoted the opportunistic screening of mental health disorders in this group of patients and their referral using existing resources. 174 Other ongoing initiatives are using mHealth technologies to treat mild to moderate depressive symptoms among patients with cardiometabolic conditions.…”
Section: Improving Healthcarementioning
confidence: 99%
“…[163][164][165][166][167][168][169] Different projects have been working towards improving the health system, at all levels (primary care, hospitals or specialized institutes) and working with all stakeholders (health workers, managers, regional health directors) to improve access to care, increase availability and affordability of medicines, improve coordination of care or improve patient satisfaction. [170][171][172][173] Given the comorbidity between mental health and cardiometabolic conditions, some projects have promoted the opportunistic screening of mental health disorders in this group of patients and their referral using existing resources. 174 Other ongoing initiatives are using mHealth technologies to treat mild to moderate depressive symptoms among patients with cardiometabolic conditions.…”
Section: Improving Healthcarementioning
confidence: 99%
“…Education can include academic detailing (one-on-one) and/or deprescribing workshops. 63,64 Although there is no evidence to suggest the value and • Antidiabetics (especially shorter-acting insulin) [21][22][23] • Antihypertensives [24][25][26][27] • Antipsychotics [28][29] • Benzodiazepines and nonbenzodiazepine sleep medications [30][31] • Opioids 36 No further perceived benefit: Medications that do not carry a current, appropriate indication or are part of a prescribing cascade or scenarios where preventive medications are unlikely to confer any patientimportant benefits over the patient's remaining lifespan after a risk & benefit evaluation 6…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist‐managed clinics (PMCs) provide outpatient services such as medication therapy management (MTM), disease management and patient education 1 . Previous studies have shown that implementing MTM has a significant impact on enhancing medication adherence, improving clinical outcomes 2–9 and achieving cost‐effectiveness 10–14 …”
Section: What Is Known and Objectivementioning
confidence: 99%